An off-line programming system for palletizing robot. (8th September 2016) - Chen, Youdong; Li, Ling; Tang, Wei
Off-line programming systems are essential tools for the effective use of palletizing robots. This article presents a dedicated off-line programming system for palletizing robots. According to the user practical requirements, there are many user-defined patterns that can't be easily generated by commercial off-line robot programming systems. This study suggests a pattern generation method that users can easily define their patterns. The proposed method has been simulation and experiment. The results have attested the effectiveness of the proposed pattern generation method.